ANALISIS DETERMINAN SOSIOEKONOMI TERHADAP POLA KONSUMSI PANGAN RUMAH TANGGA PETANI KELAPA SAWIT DI DESA GADING SARI KECAMATAN TAPUNG KABUPATEN KAMPAR (Analysis of Socioeconomic Determinant of Food Consumption Patterns Among Oil Palm Farming Household in Gading Sari Village, Tapung District, Kampar District) - RASIHEN, YOGY; PRAMONO, AGUNG; PUTRI, DINI AMALIA; KURNIATY, TRI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
The relationship between consumption and income level was reciprocal, where increased income led to higher food consumption, while lower income resulted in reduced consumption. This study aimaed to analyze the relationship between income levels, education, number of family members, and land area in influencing farmers’ food consumption patterns. The research was conducted in Gading Sari Village, Tapung District, Kampar Regency, Riau Province. A Simple Random Sampling (SRS) method was employed with 52 respondents. Results revealed that the average monthly income of farmers was IDR 7,678,651, while their average monthly food expenditure amounted to IDR 1,714,231. The simultaneous F-test indicated that the independent variables (income, education, family size, and land area) collectively had a significant effect on food consumption patterns. However, partial analysis demonstrated that only income and family size significantly influenced dietary habits, whereas land area and education showed no statistically significant correlation with farmers’ food consumption patterns.